(untitled) (Journal of the College of Education for Women, 2019)
The purpose of this research is to identifythe effect of the translation of poetic poem into an artistic picture in the achievement of retention among fifth grade students.In order to verify the research goal, the first two hypotheses were determined. There are no statistically significant differences between the average scores of the experimental group who study (according to the technical picture) ) And the control group (according to the traditional method of art education) at the level of significance (0,05). The second is that there are no statistically significant differences between the average of the experimental group who study (according to the technical picture) and the control group who study (On According to the traditional method in the subject of education) at the level of significance (0,05) in the retention of the test of the post and the third are no significant differences between the average score of the experimental group who study (according to the technical image) at the level of significance (0,05) Tribal and post-test .The research community was determined by the fifth grade students in the Directorate of Education of Karkh II (1770). The sample was chosen from the secondary students of(HalaBintKhuwailid). The number of students in the experimental group for the purpose of equivalence was( 24) students and the control group was( 24) students. The researcher used the( T-test) for two independent samples, the coefficient of difficulty and discrimination, the effectiveness of the alternatives, and the alpha-kronbach equation for the stability of the test and the conclusion of the experiment. For the researcher several results, the most important of the experimental group on the control on the basis of the translation of the poetic poem to a technical image to increase the conservation of students through the involvement of more than a sense in the process of learning, which leads to the consolidation of this learning and deepening as well as develop their ability to reflect and accuracy of observation and therefore recommended the researcher Using the technical image in the presentation of the educational material, in order to prove its effectiveness in retaining the conservation of the students and suggested the researcher to conduct a study on the role of artistic image in literature for the fourth grade preparatory